Wintering heifer calves that are to be fattened for the fall market. - Smith, E.F.; Good, D.L.; Cox, R.F.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2012)
Thirty good quality Hereford heifer calves, 10 head to a lot, are being used in this study. They were delivered to Manhattan, Kansas, on September 15, 1952, at a cost of 29 cents per pound. They originated in the Sterling City, Texas, area. From delivery date until November 15, 1952, they were fed prairie hay and 1 pound of soybean oil meal pellets per head daily. The system of management planned for each lot follows. Lot 19-Wintered on brome pasture supplemented when necessary with protein; grazed on brome pasture until July 15; full-fed in the drylot 100 days. Lot 7-Wintered on dry bluestem pasture supplemented with 1 ½ to 2 pounds of concentrate feed per head daily; grazed on bluestem pasture until July 15; full-fed in drylot 100 days. Lot 8-Wintered on Atlas sorgo silage, prairie hay, 1 pound of soybean pellets and 2 pounds of corn per head daily; grazed on bluestem pasture May 1 to July 15; full-fed in drylot 100 days.
Keywords: Beef; Protein; Heifer; Gain